2023
DOI: 10.15446/dyna.v90n230.111829
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on nanotechnology applied to carbon capture, use and storage in the oil and gas industry

Lady J. Giraldo,
Camilo A. Franco,
Farid B. Cortés

Abstract: La industria petrolera mundial está llamada hoy en día a realizar operaciones carbono neutrales que permitan reducir la cantidad de emisiones de CO2 actuales. Sin embargo, existen diferentes limitaciones técnico-económicas que impiden avanzar hacia tecnologías de captura, uso y almacenamiento de carbono (CCUS por sus siglas en inglés) con niveles de desarrollo (TRL por sus siglas en inglés) altos que permitan su escalamiento bajo condiciones reales. Es así que la nanotecnología ha tomado un importante protagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Another opportunity consists of developing biosurfactants and bionanoparticles for CEOR processes or even for applications in mobility control in CO 2 -EOR processes, implying important benefits in reducing the CO 2 footprint and using CO 2 with possibilities of underground sequestration. 86 Also, nanotechnology can offer solutions by designing carbon quantum dot nanomaterials (CQDs) with exclusive fluorescence properties. Recent studies 21,87,88 have shown that CQDs can be injected to know the connectivity of the patterns, and even through integration into the CEOR processes, the arrival time of the surfactant can be determined.…”
Section: Modified Capillary Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Another opportunity consists of developing biosurfactants and bionanoparticles for CEOR processes or even for applications in mobility control in CO 2 -EOR processes, implying important benefits in reducing the CO 2 footprint and using CO 2 with possibilities of underground sequestration. 86 Also, nanotechnology can offer solutions by designing carbon quantum dot nanomaterials (CQDs) with exclusive fluorescence properties. Recent studies 21,87,88 have shown that CQDs can be injected to know the connectivity of the patterns, and even through integration into the CEOR processes, the arrival time of the surfactant can be determined.…”
Section: Modified Capillary Numbermentioning
confidence: 99%
“…Further, reservoir simulation strategies, including history matching, should be coupled with data science and machine learning to have a broader panorama of the oil declining rate and how different operational variables affect the well performance. Another opportunity consists of developing biosurfactants and bionanoparticles for CEOR processes or even for applications in mobility control in CO 2 -EOR processes, implying important benefits in reducing the CO 2 footprint and using CO 2 with possibilities of underground sequestration . Also, nanotechnology can offer solutions by designing carbon quantum dot nanomaterials (CQDs) with exclusive fluorescence properties.…”
Section: Laboratory Tests For Nanofluid Designmentioning
confidence: 99%